PW 0211 Impact of child-friendly activities on patient satisfaction in the pediatric emergency department of a low to middle income country. (November 2018) - Naeem, Rubaba; Bhimani, Salima Ahmed; Feroz, Asher; Khan, Uzma R; Mian, Asad I
Abstract : Child- and family-centered care in the Pediatric Emergency Department (PED) is imperative for patient quality and safety, as well as for allaying anxiety in both parents and their children. To assess satisfaction of children before and after introduction of child-friendly activities in PED of a low-resource country. This was an interventional trial conducted at Aga Khan University PED, Karachi, Pakistan, between October 2014 and February 2015. Children (6 months – 16 years) presenting to PED and categorized as priority levels 3–5 per Emergency Severity Index were enrolled in two phases. No intervention was provided in first phase (control group). In second phase, after a month, age-appropriate, low cost child-friendly activities were introduced (intervention group). Satisfaction was gauged using the modified Wong-Baker scale administered to patients (over 6 years) or parents (with children under 6 years), by pre-trained data collectors before and after introduction of child-friendly activities in PED. There were 303 patients enrolled in each group. Mean age was around 5 years, with over half male, for both groups. No significant difference was observed in mean satisfaction levels for overall treatment between the two groups (2.2 in control vs 2.3 in intervention). Although patients most commonly presented with pain to the PED, no significant difference was observed between the groups for degree of pain/fear. Child-friendly activities in the PED did not improve patient satisfaction. Additional strategies are needed to help the pediatric population deal with emotional turmoil during their visits to the low-resource PED